Do government grants promote innovation efficiency in China's high-tech industries?. (November 2016) - Hong, Jin; Feng, Bing; Wu, Yanrui; Wang, Liangbing
Abstract: Despite extensive discussion about the important role of government in enterprise development, the function of government grants in the innovation activities of high-technology (high-tech) industries is still unclear. In this paper, the stochastic frontier model and a unique panel data set of 17 high-tech industries in China spanning the 2001–2011 period are applied to explore how government grants affect the innovation performance of these industries. Results indicate that the innovation efficiency of high-tech industries rapidly improved in the past decade. However, it is found that government grants exert a negative influence on innovation efficiency of high-tech industries. However, the impact of private R&D funding is significant and positive. Furthermore, when the high-tech industries are grouped into five sub-industries, the results show that government grants had different effects on the innovation in each sub-industry. Highlights: Government grants have a negative impact on innovation of China's High-tech Industry. Private R&D funding and other funds cast positive effect on innovation. Government grants have different impacts on innovation of different sub-industries. The innovation efficiency of High-tech industry grew rapidly but is relatively low.